Relevansi Penerapan Prinsip Mengenali Pengguna Jasa Terhadap Kewenangan Notaris - Annisa Septia Puspareni; Fifiana Wisnaeni (Program Studi Magister Kenotariatan, Fakultas Hukum, Universitas Diponegoro, 2023)
AbstractThe Notary besides having the authority to make an authentic deeds, they also have the authority to identify their service users. This study aims to know the relevancy between implementation’s principle of recognizing service users, based on Permenkumham No. 9 of 2017 with the Notary’s authority and the legal consequences for a Notary who does not apply this principle. The method in this study is used normative research. The results of the study indicate the Notary’s authority to apply the principle of recognizing service users is the attribution authority obtained from Permenkumham No. 9 of 2017 and the legal consequences for a Notary who does not apply this principle, may be subjected to an administrative sanctions based on the UUJN.Keywords: notary; authority; service userAbstrakNotaris selain memiliki kewenangan untuk membuat akta otentik juga memiliki kewenangan untuk mengenali pengguna jasanya. Artikel ini bertujuan untuk mengetahui relevansi penerapan prinsip mengenali pengguna jasa berdasarkan Permenkumham No. 9 Tahun 2017 terhadap kewenangan Notaris dan akibat hukumnya bagi Notaris yang tidak menerapkan prinsip tersebut. Metode penelitian yang digunakan adalah penelitian normatif. Hasil menunjukkan bahwa kewenangan Notaris untuk menerapkan prinsip mengenali pengguna jasa merupakan kewenangan atribusi yang diperoleh dari Permenkumham No 9 Tahun 2017 dan akibat hukum bagi Notaris yang tidak menerapkan prinsip tersebut adalah Notaris dapat dikenakan sanksi administrasi berdasarkan UUJN.Kata kunci: notaris; kewenangan; pengguna jasa